Bioremediation of Congo red dye in immobilized batch and continuous packed bed bioreactor by Brevibacillus parabrevis using coconut shell bio-char - Abu Talha M.; Goswami M.; Giri B.S.; Sharma A.; Rai B.N.; Singh R.S. (My University, 2025)
In the present study, bacterial species capable of degrading colour waste were isolated from the water bodies located near the carpet cluster in the Bhadohi district of U.P., India. Among the isolated species best one was selected on the basis of its capability to degrade Congo red in batch experiments using NaCl-Yeast as the nutrient media and further it was identified as Brevibacillus parabrevis using 16S rDNA sequencing. The process parameters were optimized for maximum degradation in batch experiments and found out to be: Inoculum size: 3 ml, Temperature: 30 °C, Time: 6 days leading to a removal of 95.71% of dye sample. The experiment showed that bacteria immobilized with coconut shell biochar in continuous mode showed much better degradation than batch study without immobilization. The kinetics parameters μmax, Ks, and [Formula presented] were found to be 0.461 per day, 39.44 mg/day, and 0.0117 L/mg/day using Monod model. © 2017 Elsevier Ltd